1997
DOI: 10.1073/pnas.94.4.1591
|View full text |Cite
|
Sign up to set email alerts
|

Why do mitochondria synthesize fatty acids? Evidence for involvement in lipoic acid production

Abstract: The function of acyl carrier protein (ACP) in mitochondria isolated from pea leaves has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
163
2
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(173 citation statements)
references
References 43 publications
(34 reference statements)
7
163
2
1
Order By: Relevance
“…In this study we prepared a polyclonal antibody specific to lipoic acid synthase of Arabidopsis and investigated its intracellular localization in Arabidopsis cells. The obtained results demonstrated that lipoic acid synthase is present in mitochondria, suggesting that the biosynthesis of lipoic acid takes place in mitochondria, which is consistent with the previous observation that a major part of de novo synthesized fatty acids in mitochondria may be used for biosynthesis of lipoic acid (Wada et al, 1997).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In this study we prepared a polyclonal antibody specific to lipoic acid synthase of Arabidopsis and investigated its intracellular localization in Arabidopsis cells. The obtained results demonstrated that lipoic acid synthase is present in mitochondria, suggesting that the biosynthesis of lipoic acid takes place in mitochondria, which is consistent with the previous observation that a major part of de novo synthesized fatty acids in mitochondria may be used for biosynthesis of lipoic acid (Wada et al, 1997).…”
Section: Discussionsupporting
confidence: 80%
“…Octanoic acid has been shown to be the precursor of the carbon chain (White, 1980;Parry, 1983), but neither the origin nor the mechanism whereby the sulfur atoms are inserted into the carbon chain is known. We recently investigated the function of mitochondrial ACP, which was discovered in the mitochondria of several organisms (Shintani and Ohlrogge, 1994;Schneider et al, 1997), and found that it is involved in the biosynthesis of fatty acids in mitochondria of pea and Neurospora (Wada et al, 1997). We also found that octanoyl-ACP is synthesized in mitochondria as an intermediate of fatty acid synthesis and may be used for the biosynthesis of lipoic acid (Wada et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we cannot entirely exclude the possible presence of a small fraction of HNE-modified peptides in our preparations, limited bias caused by HNE would not weaken but even strengthen our argumentation. H protein of GDC is the dominant lipoylated protein in photosynthesizing plant cells and occurs in large amounts in green leaf mitochondria, representing the major sink for octanoyl chains in these organelles (Wada et al, 1997;Gueguen et al, 2000;Taylor et al, 2004). On the other hand, roots contain only very small amounts of GDC (Douce et al, 2001) and do not require high levels of lipoate biosynthesis.…”
Section: Mtkas Is Important But Not Obligatory For Lipoylation Of Mitmentioning
confidence: 99%
“…Here, we report on the identification of the gld1 locus (now designated mtkas-1) and show that it resides on gene At2g04540 encoding b-ketoacyl-[acyl carrier protein (ACP)] synthase (mtKAS; EC 2.3.1.41), a key enzyme of mitochondrial fatty acid biosynthesis (Wada et al, 1997;Gueguen et al, 2000;Yasuno et al, 2004). One of the major products of mtKAS, octanoyl-ACP, is required for the lipoylation of essential mitochondrial proteins including the H protein of GDC and the dihydrolipoyl acyltransferase (E2) subunits of the pyruvate dehydrogenase (PDH) and a-ketoglutarate dehydrogenase (KGDH) multienzyme complexes.…”
mentioning
confidence: 99%